THE IMPACTS OF FAKE MARRIAGE IN TESS WAKEFIELD'S NOVEL PURPLE HEARTS - Pohan, Rahmad Dani; Pardi, Pardi (JOURNAL OF LANGUAGE, 2025)
Fake marriages, though often portrayed as harmless arrangements in fictional narratives, can lead to complex and far-reaching consequences in the lives of the characters involved. This study aims to explore the negative impacts of a fake marriage on the protagonist’s life in Tess Wakefield’s novel Purple Hearts. Employing a qualitative descriptive approach, the study uses M.H. Abrams’ theory of literary analysis as its primary analytical framework. Additional relevant theories are incorporated to support the interpretation of the data. The analysis reveals that the fake marriage in the novel results in several negative consequences, including legal, financial, and emotional repercussions. The protagonist engages in the marriage to resolve personal financial difficulties. Despite these challenges, the characters—Cassie and Luke—eventually develop genuine affection, suggesting a transformative journey shaped by their experiences. The study highlights how a fake marriage, initially entered into for practical reasons, can evolve into a meaningful relationship, albeit through significant personal and relational struggles. These findings underscore the complex emotional and ethical dimensions of such arrangements in contemporary fiction.